Inwentarz dóbr konwentu zwierzynieckiego w roku Pańskim 1722 spisany - Kazusek, Szymon (Nasza Przeszłość, 2013)
The subject of this publication is the only remaining early-modern inventory of the estates of the convent of Premonstratensians at Zwierzyniec near Cracow. This manuscript contains the description of the real estates in twenty villages being in the property of the Zwierzyniec convention in 1722. The inventory is an excellent source for the research on the farm economy in convent estate. The names of convent villages which the described real estates come from have in huge majority endured until contemporary times. At present some places are within the administrative borders of Cracow, Krzeszowice or Będzin, other exist under previous or modified names, whereas one of the described villages (Zakościele) has not remained until present times. Analysing the content of the inventory it is possible to obtain detailed information about the size, the state and the organisation of the buildings that were convent property, as well as about the leases and their financial aspects. The image emerging after studying the inventory shows a wide diversity of technical condition of farm buildings. What is more, the presented description includes information about buildings in very bad state as well as about renovated or new ones.
Keywords: zwierzyniec

Sainte-Marie de Pleine-Selve en Gironde : nouvelles recherches sur une abbaye méconnue de l’ordre de Prémontré - Masson, Juliette (Bulletin du centre d’études médiévales d’Auxerre | BUCEMA, 2013)
L’opération archéologique sur le site de l’abbaye de Pleine-Selve a été programmée dans le cadre d’un doctorat portant sur les fondations liées à l’archevêque de Bordeaux Geoffroy du Loroux (1136-1158) . Seuls subsistent aujourd’hui des vestiges de l’église abbatiale, les bâtiments conventuels ayant totalement disparu. Deux sessions ont été menées en 2007 et en 2008, financées par le Service régional de l’archéologie d’Aquitaine et le Conseil général de Gironde, pour conduire une étude arché...
Keywords: pleineselve

A Norbert for England: Holy Trinity and the Invention of Robert of Knaresborough - Easterling, Joshua (Journal of Medieval Monastic Studies, 2013)
This essay considers the relationship between two monastic vitae and their historical subjects. The prose vita of the English hermit Robert of Knaresborough that is extant in London, British Library, MS Egerton 3143 contains a number of passages borrowed from the Vita B of Norbert of Xanten, the founder of Premontre. These two otherwise unaffiliated figures of religious reform are connected through Robert’s biographer, most likely a brother of the late-established Trinitarian Order, who extracted key details from Norbert’s vita to shape Robert in the founder’s image. In Egerton’s prose vita, Robert is ultimately made to serve as a legitimate origin for, and as a founder of, the Trinitarian Order at Knaresborough.
Publisher: Brepols Publishers
Keywords: 👤 norbert of xanten

Prämonstratenserkloster Heiligenthal (Heimat- und Kulturverein Gellersen, 2013)
Keywords: heiligenthal

Willkommen in Kloster Oelinghausen (2013)
Keywords: oelinghausen

Le domaine de l'abbaye Notre-Dame de Bonne-Espérance et la paroisse de Gentinnes - Annaert, Philippe (Revue d'histoire du Brabant wallon, 2013)
Keywords: bonne-espérance

Fverte como vn león: el Monasterio de San Leonardo de Alba de Tormes entre la historia y la leyenda - Arnaiz Ecker, Juan José (Ediciones de la Diputación de Salamanca, 2013)
OCLC: 870173959
Keywords: alba de tormes

Bases et chapiteaux inédits de l'ancienne abbaye de la Case-Dieu - Balagna, Christophe (Actes de la première journée de l'Archéologie et de l'Histoire de l'Art de l'Isle-Jourdain (2012), 2013)
Keywords: case dieu

Recherches et découvertes archéologiques récentes à l’abbaye de Beauport (1995-2012) - Ballini, Annie-Claude (Mémoires de la société d'histoire et d'archéologie de Bretagne., 2013)
Keywords: beauport

Kloster Schäftlarn und die Entstehung der Stadt München - Bauer, Richard (Historiker) (Studien und Mitteilungen zur Geschichte des Benediktinerordens und seiner Zweige, 2013)
Keywords: schäftlarn

Die Stiftspfarrei Ilbenstadt: konfessionelle Konflikte zwischen Kurmainz und Burg Friedberg - Bewerunge, Norbert (Archiv für mittelrheinische Kirchengeschichte, 2013)
Keywords: ilbenstadt

De Norbertijnen van de O.-L.-Vrouwabdij van Mol-Postel: biografisch lexicon 12de - 21ste eeuw - Billiaert, Ivo Reginald (Studium Generale, 2013)
Keywords: postel

Uzos da Igreia da Ermida do Paiva - Carvalhal, Marta; Azevedo, Eufemia (Junta de Freguesia da Ermida, 2013)
Keywords: ermida do paiva

Keferloh: Nebenkirche St. Aegidius - Dennemarck, Hans-Jürgen; Jocher, Norbert (Erzbischöfliches Ordinariat, Ressort Bauwesen und Kunst, 2013)
OCLC: 873393560
Keywords: keferloh

Das Verhältnis der Mainzer Erzbischöfe zu den Prämonstratensern im Mainzer Schisma und seine Vorgeschichte - Ehlers-Kisseler, Ingrid (Analecta Praemonstratensia, 2013)
Keywords: 🇩🇪 germany (general)

Über den Dächern von Hüttengesäß: der Kirchturm der evangelischen Kirche Hüttengesäß und seine Glocken - Erdt, Reiner (Ronneburger Heimatblätter, 2013)
Keywords: hüttengesäß

Activités autre-Manche des cisterciens de Bégard et des prémontrés de Beauport des origines à 1414 - Evans, Claude (Mémoires de la Société d'histoire et d'archéologie de Bretagne, 2013)
Keywords: beauport

Das vergessene Kloster in Hopels: Beitrag zur Klostergeschichte des Prämonstratenserordens in Ostfriesland - Frees, Karl-Heinz (s.n., 2013)
Keywords: hopels

Abbaye Notre-Dame du Lieu-Dieu-en-Jard - Gilbert, Pierre (Patrimoine du pays jardais, 2013)
Keywords: lieu-dieu-en-jard

L'institutionalisation des religieuses dans les ordres de Prémontré et de Cîteaux (XIIe-XIlle siècles) - Grélois, Alexis (La place et le rôle des femmes dans l'histoire de Cluny : en hommage à Ermengarde de Blesle, mère de Guillaume le Pieux : actes du colloque de Blesle des 23 et 24 avril 2010, 2013)
Keywords: 📚 premonstratensian (general)

A 14th-Century Sculpted Arcade from Coverham Abbey - Harrison, Stuart A. (Journal of the British Archaeological Association, 2013)
Keywords: coverham

De invloed van de abdij van Floreffe in Houthalen en Overpelt - Hendriks, Giel (Invloed van Waalse norbertijnenabdijen in Limburg: Beaurepart en Floreffe, 2013)
Keywords: floreffe

Westbauten als Orte von Totengedenken: Konzepte zur memoria im Westbau des Klosterbasilika Ilbenstadt und im Westchor des Naumburger Doms - Heß, Pascal (Saale-Unstrut-Jahrbuch. Jahrbuch für Kulturgeschichte und Naturkunde der Saale-Unstrut-Region, 2013)
Keywords: ilbenstadt

Beaurepart - Janssens, Herman (Invloed van Waalse norbertijnenabdijen in Limburg: Beaurepart en Floreffe, 2013)
Keywords: beaurepart

De abdij van Floreffe (1121-1796): Beknopte situatieschets - Janssens, Herman (Invloed van Waalse norbertijnenabdijen in Limburg: Beaurepart en Floreffe, 2013)
Keywords: floreffe

Invloed van Waalse norbertijnenabdijen in Limburg : Beaurepart en Floreffe - Janssens, Herman (Werkgroep Norbertijner geschiedenis in de Nederlanden, 2013)
Keywords: beaurepart; floreffe

Die Wirtschaft der Steinfelder Prämonstratenser - Joester, Ingrid (Analecta Praemonstratensia, 2013)
Keywords: steinfeld

A türjei premontrei prépostság templomának falkép-restaurátori kutatása - József, Lángi (Ko kövön: David Ferenc 73. születésnapjára, 2013)
[Die Erforschung der Wandmalereien und Fassungen in der Kirche der Prämonstratenser-Propstei zu Türje]
Keywords: türje

Leitzkau: Stiftskirche "Sancta maria in monte" - Knape, Rose-Marie (Straße der Romanik: eine Entdeckungsreise ins Deutsche Mittelalter, 2013)
Keywords: leitzkau

Drei Ablaßurkunden für das Prämonstratenserstift Pöhlde aus dem 13. Jahrhundert - Könighaus, Waldemar (Archiv für Diplomatik, 2013)
Keywords: pöhlde

Vlastnosti historického zdicího materiálu - Krejčí, Šárka (Technická univerzita Ostrava, 2013)
Koncentrace památkově chráněných objektů na území České republiky je velmi vysoká, proto neustále stoupá zájem o zachování těchto historicky cenných staveb, které se často nachází v nevyhovujícím stavu. Za účelem obnovy památky se provádí stavební, historické a architektonické průzkumy, jejíchž cílem je, mimo jiné, identifikovat a specifikovat použité historické materiály. Hlavní nosnou konstrukcí památkových objektů je obvykle zdivo, které stejně jako ostatní materiály podléhá degradaci, podpořené v mnoha případech statickými i vlhkostními problémy objektu. Ve své práci jsem se zaměřila na studium vlastností historického zdícího materiálu, který prošel degradačními procesy. Teoretická část práce je věnována historii a výrobě keramiky, druhům zděných konstrukcí, vadám a poruchám zdiva a následnému stavebně technickému průzkumu a diagnostice zdiva. Experimentální část práce byla věnována laboratorním metodám pro stanovení a vyhodnocení vlastností historického zdícího materiálu pocházejícího z objektu konventu Kláštera premonstrátů v Želivě.
Accepted: 2014-02-04T13:24:01Z Publisher: Vysoká škola báňská - Technická univerzita Ostrava
Keywords: želiv

Archeologisch booronderzoek Woldjerweg 3 en 5 te Wittewierum, gemeente Ten Boer (GR) - Krol, T.N. (DANS Data Station Archaeology, 2013)
Keywords: bloemhof

Hroznata Tepelský a jeho kult ve stredoveku a raném novoveku: strucný prehled výsledku bádání - Kubín, Petr (Historická dílna, 2013)
Keywords: 👤 hroznata of bohemia

Rola przedstawień drzewa genealogicznego zakonu w środowisku premonstratensów - Kwiatkowska-Frejlich, Lidia (Archiwa, Biblioteki I Muzea Kościelne, 2013)
The commonly known representation of Tree of Jesse, as inspired by the words „And the wand will come out of the root of Jesse and a flower will grow out of from its root” (Isaiah 11:1), proves the interpersonal relationships with Jesus and His messianic prophecy - by indicating on David. But since the earliest times this theme has been explored in the secular art because branching limbs with characters of descendants, growing from the parents’ chest, clearly illustrate the relations resulting from successions of generations within the family framework. This kind of representations was also popular in orders. At that time they not only provided the information on the background of spiritual path but also the assurance of its effectiveness on the way to reach Heaven. The images of the Order of Canons Regular of Prémontré, also known as the Premonstratensians, elaborated upon in this paper, was to make canons regular believe that abiding by the rules and laws made by the Order and praising the Eucharist, canons regular may master themselves to perfection and the saints of the order, who had already successfully fulfilled this recommendation, were the best teachers on the path of spiritual progress.
Keywords: 📚 premonstratensian (general)

Der Reformversuch im Kloster Cappenberg - Lackmann, Heinrich (Verl.-Haus Monsenstein und Vannerdat, 2013)
OCLC: 867872850
Keywords: cappenberg

Autour de la naissance de l'abbaye de Beauport - Le Bonniec, Yves (Mémoires de la Société Historique et Archéologique de Bretagne, 2013)
Keywords: beauport

Zum Weingartenbesitz und Weinbau des Prämonstratenserstiftes Osterhofen in Krems an der Donau und Umgebung - Lickleder, Hermann (Deggendorfer Geschichtsblätter, 2013)
Keywords: osterhofen

De norbertijnen in Rekem: verdwenen maar niet vergeten - Maesen, Mathieu (Invloed van Waalse norbertijnenabdijen in Limburg: Beaurepart en Floreffe, 2013)
Keywords: rekem

Bývalý premonstrátský klášter v Brne - Zábrdovicích: (poznámky ke stredovekým stavebním dejinám) - Merta, David (Kláštery ve stredovekých mestech strední Evropy: Archeologické výzkumy na památkových objektech = Archaeological excavations at protected monuments, 2013)
[Former Premonstratensian monastery in Brno - Zábrdovice (remarks on medieval buildlng history)]
Keywords: zábrdovice

Hugo van Fosses als kanunnik in Fosses-la-Ville en Cambrai (1087/95-1121/23). Bijdrage tot de ontstaansgeschiedenis van de Orde van Prémontré - Mingroot, Erik van (Analecta Praemonstratensia, 2013)
Keywords: 👤 hugh of fosses

O dawnych zwyczajach prawnych w swietle materialów procesovvych klasztoru sw. Wincentego na Oibinic we Wroclawiu z XIV wieku - Mlynarska-Kaletynowa, Marta (Z badan nad kultura spoleczenstw pradziejowych i wczesnosredniowiecznych: ksiega jubileuszowa dedykowana profesorowi Boguslawowi Gedidze, w osiemdziesiata rocznice urodzin przez przyjaciól, kolegów i uczniów, 2013)
Keywords: wrocław

El aprovechamiento del agua en el monasterio de San Pelayo de Cerrato. Contexto histórico y aproximación a partir de los referentes arqueológicos - Moratinos García, Manuel; Palomino Lazaro, Ángel Luis (Monasterios y recursos hídricos en la Edad Media, 2013)
Num Pages: 163 Pp.
Keywords: san pelayo de cerrato

Besitz und Personal des Klosters Trostadt - Mötsch, Johannes (Jahrbuch des Hennebergisch-Fränkischen Geschichtsvereins, 2013)
Keywords: trostadt

Klášter premonstrátů Teplá. Osobnosti vědy a školství - Nováková, Markéta (University of West Bohemia, 2013)
Práce se zabývá vznikem, vzestupem a historií premonstrátského řádu na území Čech, konkrétněji pak kláštera Teplá. Vyzdvihuje zakladatele tohoto kláštera blahoslaveného Hroznatu. Poukazuje na nevšední význam osobností vědy, kultury a školství, které v kláštere působili.Zdůrazňuje na jejich odkaz.Práce se dále přiblíží jejich práci - byli zakladatelé mnoha škol a nejvýznamnějšími šiřiteli vzdělání v západočeském regionu.Práce se také věnuje knihovní sbírce.
Accepted: 2014-02-06T12:45:44Z Publisher: Západočeská univerzita v Plzni
Keywords: teplá

Looking Anew at the curvilinear tracery of the Bellapais Abbey Cloister - Olympios, Michalis (Cahiers du Centre d'Études Chypriotes, 2013)
Keywords: bellapais

Die Anfänge der Prämonstratenser in Franken - Petersen, Stefan (Frankenland, 2013)
Keywords: 🇩🇪 germany (general)

Un bréviaire monumental de 1139 destiné aux prémontrés (?) de Knechtsteden (?) (Codex Bruxellensis 104) - Philippart, Guy (Amicorum societas: mélanges offerts à François Dolbeau pour son 65e anniversaire, 2013)
Keywords: knechtsteden; 🛐 liturgy

Fundacja Opactwa Premonstratensów w Brzesku-Hebdowie - Podgórska, Arkadia (Meandry Historii: Starożytność – średniowiecze – nowożytność. Referaty wygłoSzone na XX ogólnopolskim zjeździe Historyków Studentów w Katowicach, 2013)
Keywords: brzesko

Stredoveká sakrálna architektúra v Bíni : (sumarizácia, korekcia a doplnenie súčasných poznatkov) - Pomfyová, Bibiana; Samuel, Marián; Žažová, Henrieta (Archaeologia historica, 2013)
Príspevok prezentuje najnovší stav poznatkov o stredovekej sakrálnej architektúre v katastri obce Bíňa. Ako ukazujú výsledky archeologických výskumov, lokalita s polykultúrnym osídlením v praveku a včasnej dobe dejinnej zaujímala dôležité postavenie v rámci včasnostredovekej sídliskovej štruktúry na území dnešného Slovenska. Dôležitosť lokality potvrdzuje aj prítomnosť štyroch stredovekých sakrálnych stavieb v katastri dnešnej obce. Dve stavby – bývalý Kostol premonštrátskeho kláštora zasvätený Panne Márii a Rotunda Dvanástich apoštolov v jeho blízkosti sa zachovali dodnes. Súčasťou kláštora bola s najväčšou pravdepodobnosťou aj Kaplnka sv. Kataríny, známa len vďaka novovekým písomným prameňom. Kaplnka zanikla spolu s východným krídlom kláštora v dôsledku eróznej činnosti rieky Hron. Archeologicky odkrytý Kostol sv. Mikuláša v polohe "Opátske" bol súčasťou zaniknutej stredovekej dediny Leánd.
Accepted: 2013-10-14T08:30:27Z
Keywords: bíňa

Klášter premonstrátek v Doksanech a Slánsko : Slánské rozhovory 2012 - Přibyl, Vladimír; Vychodil, Pavel; Přibylová, Dana (Vlastivědné muzeum Slaný, 2013)
Keywords: doksany

Analýza historických malt a omítek ve zdivu budov kláštera Želiv - Rezek, Petr (Technická univerzita Ostrava, 2013)
Při rekonstrukcích nebo obnově fasád objektů se z pohledu stavebního inženýra nebo technika jeví jako primární stavebně – technické problémy (např. trhliny, vlhkostní problémy). Součástí identifikace těchto poruch u památkově chráněných objektů před případnou rekonstrukcí, ve snaze docílit podobného složení materiálu, je průzkum a analýza jeho použitých surovin. Identifikace materiálového složení omítek a malt představuje nezbytnou součást hodnocení historických fasád památkově chráněných objektů. Předložená diplomová práce se zabývá analýzou odebraných omítek některých objektů Kláštera premonstrátů s kostelem Narození P. Marie v Želivě.
Accepted: 2014-02-04T13:23:37Z Publisher: Vysoká škola báňská - Technická univerzita Ostrava
Keywords: želiv

Nouvelles observations sur l'abbaye de Beauport - Rioult, Jean-Jacques (Mémoires de la Société d'Histoire et d'Archéologie de Bretagne, 2013)
Keywords: beauport

Ermida do Paiva: reflexões e problemáticas - Rosas, Lúcia Maria; Botelho, Maria Leonor; Resende, Nuno (Revista da Faculdade de Letras: Ciências e Técnicas do Património, 2013)
With this article we want to reflect and discuss some of the historical issues concerning the Romanesque architecture, taking as an example the Ermida do Paiva (Castro Daire). Problems like the recovery of medieval heritage, the implantation in the territory or the foundational motivation in Portuguese history context are debated.
Keywords: ermida do paiva

Archäologie an der Straße: die Ausgrabungen im Kloster Elisabethenzell bei Rieneck - Rosmanitz, Harald; Wrobel, Kathrin (Beiträge zur Geschichte der Stadt und des Raumes Lohr, 2013)
Keywords: einsiedel

Ausgrabungen in der Klosterwüstung Elisabethenzell: Stadt Rieneck, Landkreis Main-Spessart, Unterfranken - Rosmanitz, Harald; Wrobel, Kathrin (Das archäologische Jahr in Bayern, 2013)
Keywords: einsiedel

Die präventive Konservierung mittelalterlicher Stuckarbeiten und Wandmalereien in der klimaregulierten Krypta zu St. Wiperti in Quedlinburg - Schmidt, Thomas (Wandmalereien in Krypten, Grotten, Katakomben : zur Konservierung gefasster Oberflächen in umweltgeschädigten Räumen, 2013)
Keywords: quedlinburg

"Amidst the ivy thou perceiv'st a ruin". Examining the history and development of St. Andrew's Kirk, Gullane - Sproat, Diana (Transactions of the East Lothian Antiquarian and Field Naturalists' Society, 2013)
Keywords: gullane

Klášter premonstrátů Teplá - historie a současnost - Stehlík, Jan (University of West Bohemia, 2013)
Ústředním cílem bakalářské práce je provedení charakteristiky historického vývoje Kláštera premonstrátů v Teplé a dále vylíčení současného dění tohoto kulturního a duchovního centra v oblasti západních Čech.
Accepted: 2014-02-06T12:44:56Z Publisher: Západočeská univerzita v Plzni
Keywords: teplá

Die wirtschaftlichen Aktivitäten des Prämonstratenserinnenstiftes Rumbeck - Timmermann, Fritz (Heimatblätter (Arnsberg), 2013)
Keywords: rumbeck

La Grange de Durance, le prieuré, l'église et ses peintures murales - Trézéguet, Jean-Louis (Revue de l'Agenais, 2013)
Keywords: durance

Das Leere Grab des heiligen Norbert - Ullrich, Sabine (Magdeburg : Die 99 besonderen Seiten der Stadt Sabine Ullrich, 2013)
Place: Halle (Saale) Publisher: Mitteldt. Verl., 2013, ISBN 978-3-95462-099-9
Keywords: 👤 norbert of xanten

The Bolton Scropes and Easby Abbey: a family mausoleum in context - Werronen, Stephen (Bulletin of international medieval research, 2013)
Keywords: easby

Human remains from the cloister garth of the 'Koningsveld' priory near the medieval city of Delft, ca. 1450-1572AD - Westen, A.A.; Groen, W.J.; Maat, G.J.R. (Stichting ter Financiering van Barge’s Anthropologica, 2013)
Keywords: delft

Studien zum ehemaligen Prämonstratenser(-innen)kloster Pernegg im Waldviertel (Niederösterreich) - Winkelbauer, Iris (University of Vienna, 2013)
Keywords: pernegg

Die Gründung des Klosters Oelinghausen - Wolf, Manfred (Sauerland, 2013)
Keywords: oelinghausen

Počátky premonstrátů v Čechách - Zemanová, Hana (Charles University, 2013)
The Beginnings of Premonstratensian Order in Bohemia. This thesis deals with the beginnings of Premonstratensian Order and their coming to Bohemia. At first, attention is devoted to the history which is briefly characterized by political, economic, and religious conditions in Bohemia in the first half of the twelfth century. The next chapter will take us through the life of St. Norbert, his conversion to Christianity, as well as the foundation and circumstances of the Premonstratensian Order. In this chapter, the Order's form of organisation, characteristics, and daily habits are also discussed. The subject of the fourth chapter is the establishment of the Premonstratensian Order in Bohemia. There are also discussed the persons who had the main credit for coming the Premonstratensian Order to Bohemia. It was their greatest admirer Jindrich Zdik, as well as the bishop Daniel and the provost of Steinfeld named Eberwin. The next section is dedicated to the description of the consequential creation of the first male and female monasteries in Bohemia such as Strahov, Doksany, Litomysl, Zeliv and Lounovice. There are also mentioned the first abbots and priors of these monasteries. In conclusion, there is a brief summary and evaluation of the contribution of the Premonstratensian Order.
Keywords: 🇨🇿 czechia (general)